1. `int te^t dt`

Integrate by parts. u = t and dv = e^t. Then du = 1 and v = e^t

`=te^t-int e^t dt`

`=te^t-e^t+c`

`=e^t(t-1)+c`

2. `int -e^(-2t)dt`

You could use substitution, but I like to just think "what would the derivative of e^-2t be? -2e^-2t. So we have half of that:

`1/2 e^(-2t)+c`

3. `int te^(t^2) dt`

Think "what would the derivative of `e^(t^2)` be? `2te^(t^2)` . Again, we just have half of that in our integral, so answer is

`1/2e^(t^2)+c`

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.